The monocratic decisions of the federal supreme court in times of a pandemic – the necessary sufficient deliberation - Morishita Wada, Ricardo; André Coutinho Teles, Carlos; Chow De Martino Tostes, Eduardo (Seven Editora, 2023)
The research aims to investigate the socioeconomic consequences of the monocratic decision handed down by Minister Ricardo Lewandowski in the records of ADI 6363 during the state of public calamity, from the perspective of legal certainty. From the state of exception caused by Covid-19, the study aims to verify the (un)reasonableness of the monocratic decision when faced with the judgment of the precautionary measure by the Plenary of the Supreme Court. The methodology involved the study of the Federal Constitution and the federal legislation related to the subject, the Internal Regulations of the Federal Supreme Court, jurisprudence, addition to national and foreign doctrinal sources. The results bring reflections with the purpose of promoting the rational and univocal deliberation of the Supreme Court so that it is guided by consensus and not by the isolated dispute of which of the votes should prevail over the other. Likewise, it was concluded that the precautionary decision issued in a monocratic way in the records of ADI 6363 generated significant legal uncertainty for social actors while not being reformed by the Plenary of the Supreme Federal Court. DOI: 10.56238/pacfdnsv1-109